Water reuse at the pulp and paper industry using water source diagram (Research, Society and Development, 2020)
One of the main issues in the present and upcoming decades is the improvement of natural resource use efficiencies. The industrial use of water is preferred as a target for the implementation of sustainable models of water management with the purpose of reducing the use of this resource and generates less waste. This study aims the application of the Water Source Diagram (WSD) method in paper industry, typology associated to high wastewater generation, as a potential strategy to achieve sustainable industrial processes through wastewater reuse. Operational data from paper industry were provided by previous works. Two scenarios of freshwater consumption were generated to model the system. Both cases showed that the freshwater consumption may be reduced over 30.22%, in relation to the baseline of no reuse. The efficiency of the WSD was also compared to other results reported in the literature. Although economic evaluation has not been addressed in this work, the method could be considered as a strategic tool for decision making.